Dental Caries and Habit of Eating Sweet Foods, Drinking Sweet Drinks, and Brushing Teeth Correctly in the Community Aged 15-64 Years - Made Ayu Lely Suratri; Rudi Hendro Putranto; Noerendah Pracoyo; Lelly Andayasari; Vebby Amelia Edwin; Tati Suryati (Health Science Journal of Indonesia, 2022)
Background: Dental caries is one of the dental and oral health problems that many Indonesian people complain about. Many dental caries are caused by bad habits, including consuming sweet foods and brushing teeth irregularly. The purpose of this analysis is to determine the relationship between the incidence of dental caries with the habit of eating sweet foods and sweet drinks and the habit of brushing teeth in the community aged 15-64 years in Indonesia. Methods: The research method is a further analysis of the data Riskesdas 2018 with a cross-sectional and non-interventional design. The research sample was all household members in the selected households. The samples analyzed were household members aged 15-64 years. Implementation of data collection wass done through interviews using a questionnaire. Further analysis of this data was carried out using univariate, bivariate and multivariate methods. Results: The results showed that the respondent's characteristics, that is age, gender, education, and residence had a significant relationship with the incidence of dental caries, with p-value <0.05 (p=0.0001). The habit of eating sweet foods and drinking sweet drinks and brushing teeth correctly had a significant relationship with the incidence of dental caries, with p-value < 0.005 (p= 0.0001). The results of the multivariate test, almost all factors affect the incidence of dental caries, except for the occupational factor with p-value > 0.05 (p=0.260). Keywords: Dental caries, sweet foods, sweet drinks, brushing teeth